Copper complex/polyoxometalate‐based tunable multi‐color film for energy storage. Issue 4 (2nd May 2022) - Chu, Dongxue; Qu, Xiaoshu; Zhang, Shangfei; Zhang, Jianrong; Liu, Zefeng; Zhou, Lili; Yang, Yanyan
Abstract: Polyoxometalates (POMs) are considered as an attractive option for electrochromic energy storage (EES) system due to their unique electrochemical feature. Herein, a composite film NW/P2 W17 /Cu (phen)2 based on Dawson‐type monolacunary POMs K10 P2 W17 O61 (abbreviated as P2 W17 ) and copper complex [Cu II (phen)2 ](NO3 )2 (abbreviated as Cu (phen)2 ) formed on TiO2 nanowire (abbreviated as NW) array substrate was fabricated by hydrothermal process and layer‐by‐layer self‐assembly combination method. This rational designed film NW/P2 W17 /Cu (phen)2 exhibits excellent tunable multicolor electrochromic behavior and improved pseudocapacitive performance with large optical modulation (43.7% at 600 nm), fast switching time (tc = 2.9 s, tb = 9.5 s), and high volumetric capacitance (228.0 F cm −3 at 0.3 mA cm −2 ). In the process of charge and discharge, the composite film can realize the transformation from light green to orange, green, and finally to blue‐green color, successfully achieve the bridge between electrochromic behavior and energy storage, and monitor the level of stored energy by color change. This work showed great potential of POMs‐based electrode materials for integrated electrochromism and energy storage applications.